2003
DOI: 10.1073/pnas.2132993100
|View full text |Cite
|
Sign up to set email alerts
|

Worker policing without genetic conflicts in a clonal ant

Abstract: In group-living animals, mutual policing to suppress reproduction is an important mechanism in the resolution of conflict between selfish group members and the group as a whole. In societies of bees, ants, and wasps, policing against the production of males by other workers is expected when egg laying by workers decreases the average inclusive fitness of individual group members. This may result (i) from the relatedness of workers being lower to worker-than to queen-derived males or (ii) from a lowered overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 38 publications
(31 reference statements)
2
83
1
1
Order By: Relevance
“…(Kikuta and Tsuji 1999). Worker policing has even been found in species that reproduce parthenogenetically: the ant Platythyrea punctata (Hartmann et al 2003) and the Cape honeybee Apis mellifera capensis ; but also see Moritz et al 1999;Beekman et al 2002) and also in two species where workers are equally related to the queen's sons as to other workers' sons (Vespula vulgaris and Formica fusca). In these cases, worker policing is selectively neutral on relatedness grounds.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…(Kikuta and Tsuji 1999). Worker policing has even been found in species that reproduce parthenogenetically: the ant Platythyrea punctata (Hartmann et al 2003) and the Cape honeybee Apis mellifera capensis ; but also see Moritz et al 1999;Beekman et al 2002) and also in two species where workers are equally related to the queen's sons as to other workers' sons (Vespula vulgaris and Formica fusca). In these cases, worker policing is selectively neutral on relatedness grounds.…”
Section: Discussionmentioning
confidence: 98%
“…As a result, worker policing can have colony-level benefits, particularly if policing occurs through aggression and causes reproductive workers to work rather than reproduce (e.g., in A. smythiesi [Iwanishi et al 2003] and P. punctata [Hartmann et al 2003]). Theory has shown that if worker policing has colony-level benefits, it can be selected for even under single mating (Ratnieks 1988).…”
Section: Colony-level Costs Of Worker Reproductionmentioning
confidence: 99%
See 3 more Smart Citations